Rancang Bangun Sistem Informasi Pengaduan Layanan Menggunakan Metode Rational Unified Process - Asri Mulyani; Yosep Septiana; Renaldy Alamsyah (Institut Teknologi Garut, 2022)
Integrated Islamic Elementary School (SDIT) Bina Insan Qur'ani is an A-accredited elementary school education institution located on Jl. Raya Cibatu Bandrek, RT 02 RW 06, Padasuka Village, Cibatu District, Garut Regency, West Java, 44185. In developing and improving the quality of school service complaints quickly and service satisfaction is always fulfilled, every school will of course prepare the best service for every student namely by utilizing existing information technology at this time. This is due to the unavailability of a complaint system at SDIT Bina Insan Qurani so that it can make it difficult for parents of students to provide aspirations or suggestions to the school. The purpose of this research is to create a system capable of reporting the results of complaints from the Bina Insan Quráni Integrated Islamic Elementary School (SDIT) services. This study uses the Rational Unified Process (RUP) method by going through four phases, namely inception, elaboration, construction and transition, the modeling design used is the Unified Modeling Language (RUP) modeling. In making the website using the PHP programming language, with the Laravel framework and MySQL as the database server. The results of this study are a service complaint information system that can be accessed on various browsers, with features that can assist school administrators in receiving complaints or suggestions from students' parents.